Flexible carbon nanofiber sponges for highly efficient and recyclable oil absorption1. Issue 86 (18th September 2015) - Ge, Xiang; Yang, Wei; Wang, Jitong; Long, Donghui; Ling, Licheng; Qiao, Wenming
<x xml:space="preserve">Abstract</x> Carbon nanofiber sponges composed of three-dimensional networks have been prepared though chemical vapor deposition. Such sponges exhibit controllable bulk density, admirable mechanical flexibility and high oil absorption capacity.